PROBLEMATIKA IMPLEMENTASI PMK NO. 9 TAHUN 2021 BAGI WAJIB PAJAK UMKM DI KABUPATEN SUMENEP - Moh. Faisol; Norsain Norsain (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2022)
The aims of this reseach to understand and reveal the problems of implementing PMK 09 of 2021 concerning Final Tax Incentives Borne by the Government for UMKM in Sumenep Regency. The method used is a case study with data collection techniques through observation, in-depth interviews, and documentation and analyzed using the stages of data reduction, data presentation, drawing conclusions and testing the validity of the data. The results of this study are tax incentives for UMKM are very useful in reducing the business burden that must be borne, because the tax burden that should be paid has been borne by the government. The problems faced in the implementation of PMK 09 of 2021 are First, the PPKM condition makes DJP unable to carry out direct socialization to DJP taxpayers so that information related to incentives to be conveyed is hampered because only some can participate in online socialization activities due to limited equipment. and low technological capabilities. Second, the condition of UMKM human resources has not been able to understand the application of tax incentives and finds it difficult. Due to the low level of understanding in compiling realization reports and technology in accessing the online DJP address